Efficacy of prasugrel administration immediately after percutaneous coronary intervention in ST-elevation myocardial infarction - Flierl, Ulrike; Zauner, Florian; Sieweke, Jan-Thorben; Berliner, Christine; Napp, L. Christian; Tillmanns, Jochen; Bauersachs, Johann; Schäfer, Andreas (Thrombosis and Haemostasis, 2017)
Prasugrel, a potent thienopyridine, achieves stronger inhibition of platelet activation than clopidogrel. However, onset of inhibition is significantly delayed in patients with acute ST-elevation myocardial infarction (STEMI), as haemodynamic instability and morphine application seem to exhibit significant influence. Since rapid onset of effect was demonstrated in non-STEMI patients when prasugrel was administered only after percutaneous coronary intervention (PCI) without increasing cardiovascular event rates we assessed the efficacy of prasugrel loading immediately after PCI for STEMI instead of pre-loading before revascu-larisation. We investigated 50 consecutive patients with acute STEMI (mean age 56 ± 10 years) admitted for primary PCI. Prasugrel efficacy was assessed by platelet reactivity index (PRI; VASP assay) before, 1, 2, 4, 6, 12, and 24 hours following an oral loading dose of 60 mg immediately after PCI. High on-treatment platelet reactivity (HTPR) was de-fined as PRI>50 %. Prasugrel significantly and rapidly reduced platelet reactivity in acute STEMI patients (p<0.0001 at each time point vs control). Morphine application resulted in a significantly higher HTPR rate among patients having received morphine less than 1 hour before pra-sugrel loading (p<0.001) while concomitant metoclopramide (MCP) treatment did not significantly affect prasugrel efficacy. In conclusion, in contrast to previous reports describing a significant delay in onset of prasugrel-mediated P2Y12 inhibition in acute STEMI, we observed a rapid onset with low HTPR rates comparable to those observed in stable non-STEMI patients. Prasugrel administered directly after primary PCI might therefore be a useful therapeutic strategy in patients with STEMI to provide strong and effective P2Y12 inhibition.
Keywords: STEMI; prasugrel; loading; PCI; morphine